Randomised double-blind trial of recombinant interferon-beta for condyloma acuminatum. Issue 2 (April 1996) - Monsonego, J; Cessot, G; Ince, S E; Galazka, A R; Abdul-Ahad, A K
Abstract : OBJECTIVE: To evaluate the safety and efficacy of two intralesional doses of recombinant human interferon-beta (r-hIFN-beta: Rebif, Ares Serono), given 3 times a week for 3 weeks, in the treatment of condyloma acuminatum. DESIGN: A randomised, double-blind, within-patient, placebo-controlled study. SUBJECTS: 25 patients (24 males, 1 female) with a history of condyloma acuminatum. Twenty had failed previous treatment for condyloma acuminatum. In each patient, 3 distinct lesions were selected for treatment. Each selected lesion was randomly assigned to receive intralesionally one of the following: r-hIFN-beta 33, 000 IU/day, r-hIFN-beta 1 x 10(6) IU/day, or matching placebo. SETTING: Institut Alfred Fournier, Paris, France. OUTCOME MEASURES: Response was evaluated colposcopically at the end of treatment (day 22) and 5 weeks later (month 2). Complete response (CR) was defined as disappearance of the treated lesion. Partial response (PR) was defined as at least a 50% reduction in size, but not disappearance of the treated lesion. RESULTS: The higher dose of 1 x 10(6) IU achieved significantly more complete and partial remissions than placebo, both by the end of treatment, and 5 weeks later. CONCLUSIONS: r-hIFN-beta appears to be safe and effective when administered intralesionally to patients with condyloma acuminatum. Most of the treated patients had failed previous treatments and were therefore a resistant population.